Test of three conceptual models of influence of the big five personality traits and self-efficacy on academic performance: A meta-analytic path-analysis. (1st January 2018) - Stajkovic, Alexander D.; Bandura, Albert; Locke, Edwin A.; Lee, Dongseop; Sergent, Kayla
Abstract: The Big Five personality traits and self-efficacy independently relate to a multitude of outcomes across domains of functioning. Yet, only a small number of studies examined these variables together as part of the same conceptual model, and findings are mixed. We revisit their joint relationships, and test three conceptual models of influence on academic performance of college students over a semester. Because of the key role college graduates will play in society, many have a stake in better understanding their performance. The trait model specifies that the Big Five traits influence performance directly and indirectly through partial mediation of self-efficacy. In the independent model, the Big Five traits influence self-efficacy and performance independently, without mediation of self-efficacy. In the intrapersonal model, the effects of the Big Five traits on performance are fully mediated by self-efficacy. We collected data in five samples, three Universities, and two countries, N = 875, and conducted a meta-analytic path-analysis. Self-efficacy positively related to academic performance across the models, conscientiousness and emotional stability were predictive of self-efficacy and performance in some analyses, and the significance of the other three traits was fleeting. Highlights: Self-efficacy consistently, positively and directly relates to academic performance. Conscientiousness and emotional stability relate to performance in some models. Self-efficacy mediates the Big Five traits effect on performance.